Extruded Product Based on Oat and Fenugreek and their Storage Stability - A. Wani, Sajad; Solanke, Nikhil; Kumar, Pradyuman (Current Nutrition & Food Science, 2015)
In the present study, addition of fenugreek seed powder (FSP) and oat flour (OF) were used for the production of extruded snack products with increased health benefits and good nutritional value. Based on preliminary evaluation, the experiments were conducted by varying the proportion of FSP (1-5%) and OF (3-15%) using central composite rotatable design. Properties like bulk density (BD), hardness (HD), water absorption index (WAI) and water solubility index (WSI) were significantly (p<0.05) affected by proportions of FSP and OF. Increase in the content of FSP and OF, an increase in BD and HD was observed. Whereas increased WSI was observed with the increase in OF, and increased WAI was observed with the increase in FSP. The storage studies of quality extruded product (1.65 % FSP and 5.24 % OF) showed increased moisture uptake at atmospheric storage condition as compared to the accelerated storage condition. The shelf life of the extrudates packed in aluminum lined polyethylene was higher as compared to extrudates packed in high density polyethylene that happened to be due to higher water vapor transmission rate of the high density polyethylene.
Keywords: functional properties